Physical activity and blood pressure. A cross-sectional review - Støyten, Martin (UiT Norges arktiske universitet, 2017)
Background: Hypertension is known as a major risk factor for cardiovascular disease, and the world-wide prevalence of hypertension is expected to rise to 30 % by the end of 2025. Physical activity has been shown to be a major part of the conservative treatment of hypertension, although the nature of the dose-response relationship is not known. The purpose of this study was to examine the associations between physical activity and blood pressure in the sixth survey of the Tromsø Study. Methods: Tromsø 6 is a population study performed during 2007-08 in northern Norway. The study included 12981 participators, and we analyses 9913 cases after removing cases with missing data. We used ANOVA and ANCOVA analyses to examine associations between blood pressure and physical activity using SPSS 24. Results: The unadjusted analyses showed a statistically significant inverse relationship between total physical activity and systolic blood pressure. These associations disappeared when adjusting for potential confounders. The same analyses provide no significant findings for diastolic blood pressure. Conclusion: Systolic and diastolic blood pressure was not associated with total physical activity level. Although unadjusted analyses showed an inverse relationship between systolic blood pressure and total physical activity, the significant association disappeared when adding BMI to the model, suggesting that some of the differences in mean systolic blood pressure seems to be due to lower BMI or other risk factors, rather than physical activity level.